Atosiban versus betamimetics in the treatment of preterm labour in Germany: an economic evaluation - Connolly Mark; Wex Jaro; Rath Werner (BMC, 2009)
Abstract Background The use of tocolytics is central in delaying birth; however, therapeutic options vary in effectiveness and adverse events profiles, which in turn could have consequences for medical resource use and cost of treatment. Betamimetics are commonly used tocolytic agents, but their mechanism of action affects multiple organ systems leading to numerous adverse events. The availability of an oxytocin receptor antagonist, specific for prevention of preterm labour, offers a treatment option that merits further evaluation. We aimed to compare economic implications of tocolysis using atosiban and betamimetics, considering treatment efficacy and safety, as well as cost consequences of treatment of associated adverse events. Methods A systematic literature review identified six randomised clinical trials, three of them double-blinded, comparing atosiban with betamimetics, in which tocolysis was initiated within 48 hours of admission. Cost of drug treatment was calculated based on trial protocols and German hospital drug purchase costs. G-DRG Grouper was used to obtain cost per case. The drug regimen was concordant with the German guidelines for the management of preterm labour, with two alternative modalities of fenoterol analysed: continuous or bolus administrations. Results According to the results of the meta-analysis of the three double-blinded, placebo-controlled clinical trials, atosiban and betamimetics have similar efficacy (RR = 0.99, 95%CI:0.94-1.04, p = 0.772). Compared to betamimetics, use of atosiban was associated with a significantly lower frequency of adverse events for tachycardia, palpitation, vomiting, headache, hyperglycaemia, tremor, dyspnoea, chest pain, hypocalemia and foetal tachycardia. In our economic analysis, cost savings from using atosiban versus continuous, or bolus, fenoterol was 423€ per patient from the payer's perspective. From the hospital's perspective, savings from using atosiban versus continuous fenoterol ranged from 259€ for 18 hours of tocolysis to 105€ for 48 hours; the respective values for bolus fenoterol were 244€ and 55€. In the probabilistic sensitivity analysis atosiban was cost saving versus both continuous and bolus fenoterol in 87%-100% of scenarios. Conclusion In a German setting, atosiban is cost saving versus betamimetics in the treatment of preterm labour from the payer, hospital and combined perspectives. Cost savings stem from the superior safety profile of atosiban.